2016
DOI: 10.1177/0954410016636160
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on noise radiation characteristics of pulse detonation turbine engine

Abstract: The noise radiation characteristics of two-phase pulse detonation combustor and pulse detonation turbine engine were investigated under different operating frequencies utilizing gasoline as fuel and air as oxidizer. The sound pressure data of noise radiation were presented for both single-pulse detonation combustor tube and pulse detonation turbine engine. The experimental results implied that the peak sound pressure level of PDTE exit with inner diameter being 60 mm was about 157 dB under the operating freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The results showed that the SPL of HPDE is less than that of PDE about 4 dB, and the peak SPL reduces by about 2 dB. Huang et al [17] conducted far field jet noise measurements of HPDE under different operating frequencies. The results showed that the turbine interacting with PDE could decrease the peak SPL approximately 14.2 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the SPL of HPDE is less than that of PDE about 4 dB, and the peak SPL reduces by about 2 dB. Huang et al [17] conducted far field jet noise measurements of HPDE under different operating frequencies. The results showed that the turbine interacting with PDE could decrease the peak SPL approximately 14.2 dB.…”
Section: Introductionmentioning
confidence: 99%